Issues related to interventions in farmer managed irrigation: Rehabilitation of a tank irrigation system - Sakthivadivel, Ramaswamy; Shanmugham, C.R. (1989)
Presents the findings from a pilot project study of a tank rehabilitation project in Tamil Nadu. The objectives of the study were to (1) examine the present status of the tank system and design measures to remedy the deficiencies; (2) implement the needed physical improvements and suggest measures for better water distribution and management; and (3) monitor the post rehabilitation irrigation practices adopted by farmers and evaluate their effectiveness. A comprehensive diagnostic analysis was undertaken and suggestions were made regarding the improvements needed for the physical facilities.